Correlation between blood group and autoantibodies formation in multi-transfused thalassaemia patients - Al-Mamun, A. B. M.; Ashadul Islam, M.; Fatema, Kaniz; Chakrabarty, Tonusree; Islam, Kashfia; Karim, Tanzin Ara (International Journal of Research in Medical Sciences, 2024)
Background: Thalassemia is a prevalent genetic disorder of hemoglobin synthesis, characterized by reduced production or absence of one or more globin chains, requiring frequent blood transfusions that can lead to complications such as autoantibody formation. The purpose of this study was to assess the correlation between blood group and the formation of autoantibodies in thalassemia patients who have received multiple blood transfusions. Methods: This cross-sectional study at the Department of Transfusion Medicine, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, conducted from October 2017 to September 2018, included 384 thalassemia patients who received at least 10 units of red cell concentrate. Participants were selected based on specific inclusion and exclusion criteria, with informed consent obtained. Data collection involved patient interviews, clinical examinations, and hematological tests. Statistical analysis using SPSS version 23.0 included Chi-square, Fisher’s exact, and t-tests, with significance set at p<0.05. Results: Among 384 patients, the most common blood group was B+ (46.2%). Coombs' test results showed DCT positivity in 3.1% of 384 patients, ICT positivity in 7.5%, and both DCT and ICT in 4.2%. Most patients (92.3%) had their first transfusion after age 2, with 84.6% receiving transfusions every 2-4 weeks. Conclusions: In conclusion, B positive blood group thalassemia patients receiving frequent transfusions are at a higher risk of autoantibody formation, and Rhesus phenotype-matched blood with pre-storage leukodepletion is recommended to mitigate this risk.